Implementation of a laser sensor system in a multi-robot welding cell - Suoranta, Ilkka (2021)
This master’s thesis is done for the LUT University’s laboratory of welding technology as a part of project EFREA (Energy-efficient systems based on renewable energy for Arctic conditions). One of the goals of the project is to develop solutions that ensure the quality and productivity in welding manufacturing of lightweight structures. An example of such solution is optical sensing, which is a key technology in the development of adaptable and intelligent robotic welding systems. This thesis gives an overview on the possibilities and restrictions of utilizing optical sensors in robotic welding. The typical and emerging optical sensing methods and their applications are presented in a literature review. Based on the review, optical sensors can increase the flexibility of a robot system, and ensure high weld quality under varying circumstances. Main purpose of this thesis is to implement a laser sensor system in the multi-robot welding cell of the welding laboratory. The aim is to develop methods for utilizing the laser sensor for different tasks of the welding cell, and to investigate the accuracy and usability of the developed methods. The experimental section presents methods for utilizing the laser sensor for seam finding, seam tracking and workpiece positioning in jigless welding. Functionality of the seam finding and seam tracking methods was verified with practical experiments. The workpiece positioning method was not tested in practice, but the required robot programs were created, and its functions were simulated. The experiments showed that seam finding with the laser sensor provides superior accuracy in comparison to the conventional touch sensing method. Accuracy of the seam tracking method was proven to be sufficient for ensuring high weld quality. However, disturbances caused by arc light led to significant tracking errors during welding, so further development is needed in order to realize reliable seam tracking. As a key result, development proposals for improving the usability and reliability of ...